Impact of ACE Inhibitors on Cardiac Biomarker Sensitivity in Hypertensive Patients with Non-ST Segment Elevation Acute Coronary Syndrome - Joison, Agustín N.; Barcudi, Raúl J.; Baiardi, Gustavo (Achievements and Challenges of Medicine and Medical Science Vol. 6, 2024)
Background: Patients with non-ST segment elevation myocardial infarction and the risk of mortality are associated with the sensitivity of cardiac biomarkers CK-MB, cTnI to improve their diagnosis. Objective: The present study aimed to modify cTnI and CK-MB sensitivity in hypertensive patients and to examine its association with treatment with angiotensin-converting enzyme inhibitors and beta-blockers . Methods: A descriptive and random study included 35 hypertensive patients of both sexes, admitted to the coronary unit of the "Reina Fabiola "Clinic". The variables analyzed were: body mass index (BMI) measured by (weigh/height2 ) relation, time to consultation chest pain (TPC) in hours, systolic blood pressure (SBP) in mmHg. The patients were stratified without associated pathologies (Control group), n = 13; and with only hypertension, n = 22 treated with angiotensin-converting enzyme inhibitors (n= 15), beta-blockers (n = 7). Samples of blood were collected and cardiac markers analyzed at the entrance to the coronary care unit (0 hs) and after 8, 12, 24 hs. The random variables quantitative were studied by lineal correlation, and comparisons between groups were made using ANOVA II and Sidak's post hoc test. Association of variables and percent of patients were performed with Chi-square. Results: Creatine Kinase MB activity decreased at 8 hs and Troponin I values showed a decrease in hypertensive patients treated with angiotensin-converting enzyme inhibitors concerning the control group at 0 hs. Optimal cut-points of CK-MB were 13.50, 17.00, 19.50 and 14.00 UI/L, and to cTnI 0.08, 0.17, 0.16 and 0.42 µg/ml at 0, 8, 12, and 24 hs respectively. Conclusions: Cardiac biomarkers determination is required in patients with suspected Acute coronary syndrome. Remodeling and ventricular hypertrophy states are conditions that could be modified by the use of antihypertensive drugs to modify biomarker levels and sensitivity. The study proposes an algorithm incorporating changes in cTnI levels and CK-MB activity to increase the diagnostic sensitivity in hypertensive patients.